Exclusionary by Design: Law, Lawyers, and State Harms in the UK’s Streamlined Asylum Process - Natalie Hodgson (State Crime)
In 2023, in response to the UK’s growing asylum backlog, the streamlined asylum process was introduced. This article uses the streamlined asylum process as a case study for exploring the relationship between the state, law, and lawyers in the context of state harms. The article argues that the streamlined asylum process was designed to both downplay the importance of legal advice and make it practically difficult for a person to access legal advice. In doing so, the Government undermined an important procedural protection and created a process that increased the risk that a person would be erroneously denied protection. Ultimately, the streamlined asylum process was a continuation of the Government’s exclusionary approach towards people seeking asylum and its hostility towards immigration lawyers. While the streamlined asylum process was purportedly a policy of inclusion, this article argues that the process was exclusionary by design.